Turbidity influences the recruitment of Argyrosomus japonicus to estuarine nurseries - James, Nicola Caroline; Childs, Amber-Robyn; Kemp, Justin; Wilsnagh, Shannon; Edworthy, Carla (Frontiers in Marine Science, 2022)
Estuaries serve as important nursery habitats for several coastal fishery species. The successful recruitment of larvae and early juveniles into estuaries is paramount for population persistence and maintenance. Several factors have been proposed as stimuli that could elicit a recruitment response in estuary-associated ﬁsh species. Larvae and early juveniles may trace land-based cues back to an estuary by following the olfactory concentration gradient or use other visual or acoustic stimuli. Argyrosomus japonicus is an iconic estuarine-associated species. Due to overfishing, reduced freshwater input and habitat degradation in their estuarine nursery habitat, the South African population has suffered severe stock declines. Turbidity associated with high freshwater input is thought to promote recruitment into estuaries. We used choice-chamber laboratory experiments to test the hypothesis that settlement-stage A. japonicus are attracted to turbidity rather than olfactory gradients when recruiting into estuaries. Three choice experiments (with three replicate trials each) were performed over three consecutive days. Each experiment used paired combinations of six estuarine/seawater types with varying turbidity and olfactory characteristics. For each experiment, three trials were repeated in succession with six new fish for each trial. Settlement-stage A. japonicus showed a significant preference for turbid water (with and without olfactory cues) over seawater (no olfactory cues) and clear estuary water (with olfactory cues). No clear choice was made between clear estuary water (with olfactory cues) and clear artificial seawater (without olfactory cues), suggesting that turbidity gradients are most likely the primary factor governing the recruitment of settlement-stage A. japonicus into estuaries.